Ciwaringin Batik Product Development Strategy, Cirebon Regency - Kadunci - Kadunci; Tuti - Hartati (Politeknik Negeri Semarang, 2023)
Many companies successfully do product development through structured steps and act according to: technology-push and market-pull. Product development is one of the most important and must be done by a company to ensure a product is accepted by consumers. This research’s goal is to understand product development strategy of Batik Ciwaringin from Cirebon District.Data collection in this research is using interview and observation. Key interviewee is Koperasi Serba Usaha (KSU) Anugerah Batik Ciwaringin, batik artisan, and employee of Corporate Social Responsibility (CSR) PT Indocement Tunggal Perkasa, Tbk. (PT ITP). The research is using qualitative analysis as methodology.The research found that product development strategy of Batik Ciwaringin is Batik design development and diversify product line. External factor such as CSR PT ITP also contributed to encourage an effective product development and patent 5 Batik Ciwaringin design. The design patent is Pecutan, Gribingan, Rajeg Wesi, Yusupan and Manggaran. The next step in product development is creating an icon or unique value on Pecutan design in each Batik Ciwaringin design. Also, Batik Ciwaringin is consistently developing handmade and using natural coloring . The product itself follow strict protocol on the definition of Batik by refusing printing method